2019
DOI: 10.23955/rkl.v14i2.14275
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Durian Peel Extract as A Natural Anti-Bacterial Agent

Abstract: Durian (durio zibertinus) is a native tropical fruit from Southeast Asia, especially Indonesia. Durian peel is the highest composition of durian fruit (60-75%), and is still considered as waste that causes environmental problems. This study aimed to analyze the content of secondary metabolites extract, to analyze the anti-bacterial activity of durian peel extract against gram-negative and gram-positive bacteria, and to calculate the effectiveness of durian skin durian peel extract as a natural anti-bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Lysozyme is an enzyme produced from leucocytes involved in the phagocytosis of Gram-negative bacteria [48]. Previous studies have also reported that polysaccharides extracted from durian peel can inhibit the growth of Gram-positive bacteria such as Staphylococcus aureus [8,14]. This study and these previous reports collectively indicate that polysaccharides from durian rind have broad-spectrum antibacterial properties.…”
Section: Antibacterial Propertysupporting
confidence: 65%
See 2 more Smart Citations
“…Lysozyme is an enzyme produced from leucocytes involved in the phagocytosis of Gram-negative bacteria [48]. Previous studies have also reported that polysaccharides extracted from durian peel can inhibit the growth of Gram-positive bacteria such as Staphylococcus aureus [8,14]. This study and these previous reports collectively indicate that polysaccharides from durian rind have broad-spectrum antibacterial properties.…”
Section: Antibacterial Propertysupporting
confidence: 65%
“…Durian (Durio zibethinus Murr.) is a popular fruit in many countries such as Malaysia, Philippines, Indonesia, China, and Thailand [8][9][10]. It has a thick rind that constitutes about 60-75% of the whole fruit [11], which are discarded and form part of agricultural waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 96% ethanol extract of durian flesh (D. zibethinus Murr.) can act as an antibacterial against Salmonella ATCC 14028 and B. cereus ATCC 11778 which cause diarrhea [32], [33]. The antibacterial properties of PG durian peel extract against Grampositive and Gram-negative bacteria have, therefore, begun to be used in the health and pharmaceutical industries [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 125 g/ml durian peel extract could inhibit the growth of P. aeruginosa; durian peel extract with a concentration of 25% can inhibit the growth of C. albicans [25], [26]. About 95% ethanol extract of durian peel with 6% concentration was antibacterial against S. aureus and Salmonella enteria serovar typhi [27]. The 96% ethanol extract of durian fruit (D. zibethinus Murr.)…”
Section: Discussionmentioning
confidence: 99%